The Influence of Human Resource Development and Empowerment on Employee Performance - Maulana, Abdul Aziz; Veronica, Meilin; Kurniawan, Muhammad (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2025)
This study aims to analyze the effect of human resource development (X₁) and human resource empowerment (X₂) on employee performance (Y) at PT. Hijau Lestari Raya Fibreboard, Banyuasin Regency. Human resource development includes training, skill enhancement, and continuous education for employees, while human resource empowerment focuses on increasing motivation, engagement, and autonomy in the workplace. Employee performance is measured based on productivity, efficiency, and work quality. The research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to employees of the company. The data analysis was conducted using multiple linear regression to determine the influence of the independent variables (X₁ and X₂) on the dependent variable (Y). The results indicate that both human resource development (X₁) and human resource empowerment (X₂) have a positive and significant impact on employee performance (Y). Skill development and opportunities for participation in decision-making have been proven to enhance work effectiveness and productivity. Therefore, the company is recommended to continuously improve training programs and empower employees to achieve optimal performance. Keywords: Human Resource Development, Employee Empowerment, Employee Performance, Multiple Linear Regression, PT. Hijau Lestari Raya Fibreboard